Provocative Preaching and the Ethics of the Qur'an: Critical Study of Surah An-Nahl 125 - St. Aisyah BM (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study criticizes the phenomenon of provocative da'wah on social media through the perspective of Qur'anic ethics in Surah An-Nahl verse 125. With the qualitative method of content analysis and thematic hermeneutics, the results of the study show that: (1) Provocative da'wah theologically deviates from the principles of Qur'anic da'wah and ethically violates Islamic moral values such as al-ḥilm (politeness) and ar-raḥmah (compassion); (2) The three pillars in Surah An-Nahl verse 125 offer a comprehensive communication ethics framework for digital da'wah, which is integrated with digital literacy and moral responsibility; (3) The implementation of this framework has academic implications for the development of thematic interpretation studies and digital communication science, as well as practical implications in the form of operational guidelines for dai to create a calming, unifying, and dignified digital da'wah ecosystem (rahmatan lil 'alamin).